Community Empowerment in Gorontalo Regency: Adopting the Perspective of Sustainable Livelihoods in Village Fund Allocation - Pakudu, Robin (Journal of Governance, 2024)
This study aims to determine the Community empowerment government Gorontalo adopts the perspective of sustainable livelihoods in the use of village funds. The research method uses a qualitative type. The results of the study show that of the four indicators measured, there is one indicator that is considered optimal, namely sustainability, in which all development programs whose funding sources come from village funds lead to long-term life. Meanwhile, the other three indicators, namely community-centered, poverty-focused, and participatory indicators, are considered not optimal. This can be seen from the development process that pays little attention to people's aspirations, poverty alleviation that is not successful, and development that does not involve the local community in every implementation process, from planning, implementation, and monitoring.